Cost-effectiveness of tax policies on promoting sustainable diets in Iran: a modeling study - Amin Mokari-Yamchi; Nasrin Omidvar; Manoochehr Karami; Morteza Tahamipour Zarandi; Hassan Eini-Zinab (Frontiers in Nutrition)
BackgroundImplementation of food taxes may promote sustainable diets in a society. This study estimates the potential short-term impacts of taxes on sugar and sweets (SAS), sugar sweetened beverages (SSB) and hydrogenated oil and animal fats (HOAF) in Iran through a social cost-effectiveness analysis.MethodsIn this study, three tax scenarios were evaluated, including a 25% tax on SASs, a 30% tax on SSBs, and a 30% tax on HOAFs. The data from Iran’s 2019–2020 Household Income and Expenditure Survey (HIES) were utilized, and a simulated population of 1 million individuals aged over 25 years was analyzed. Population impact fraction (PIF) was calculated to estimate the averted number of cases and Disability-Adjusted Life Years (DALYs) under each policy scenario. Additionally, the study assessed water and carbon footprints, as well as all associated costs. Cost-effectiveness was evaluated through incremental cost-effectiveness ratios (ICER) and comparison with WHO-recommended thresholds.ResultsImplementation of taxes on SASs and HOAFs resulted in reductions of 1.09 and 1.08% in water footprint, as well as 0.47 and 1.05% in carbon footprint, respectively. In terms of population health, the interventions resulted in averting 343.92 DALYs (95% UI = 318.62–369.36) for the SSB tax and 1219.01 DALYs (95% UI = 1123.05–1315.77) for the tax on HOAFs. Additionally, the tax on SASs averted 1028.09 DALYs (95% UI = 947.16–1,109). All scenarios were deemed cost-effective based on the WHO threshold for ICER, with values of 0.26 billion Rials/DALY, 0.54 billion Rials/DALY, and 0.17 billion Rials/DALY, respectively.ConclusionThe studied tax scenarios could generate substantial health gains and be cost-effective in Iran. It is recommended that policymakers consider implementing such price policies to promote healthy and sustainable diets.